Hubungan Pengetahuan dan Sikap terhadap Kejadian Keputihan pada Remaja - Oktaviani, Meli; Achyar, Khamidah; Kusuma, Inggar Ratna (Jurnal Riset Kesehatan Masyarakat, 2023)
Leucorrhoea is an unusual discharge other than blood from the vaginal canal, whether smelly or not, and accompanied by local itching. Leucorrhoea in adolescents can be caused by poor genital care. Lack of knowledge and attitudes in protecting the female area causes vaginal discharge. Efforts to improve health can be done through health education. This type of research uses a literature study or literature review with a descriptive research method. This study uses 2 databases: PubMed and Google Scholar. The search strategy method for obtaining journals uses the keywords "Relationship of Knowledge and Attitudes towards Leucorrhoea in Adolescents" or "relationship of knowledge and behavior with vaginal discharge. Furthermore, the available abstract and full text titles were screened for 21 articles and 8 suitable articles were obtained. The results of the study obtained 8 literature that examined the relationship between knowledge and attitudes towards vaginal discharge in adolescents. The conclusion of this study is that there is no significant relationship to the vaginal discharge studied.